Policy Integration for Achieving Sustainable Development Goals in Sustainability Reporting Disclosure - Ari Purwanti (Universitas Padjadjaran, 2023)
This research aims to provide an overview of how companies integrate the achievement of Sustainable Development Goals (SDGs) into their Sustainability Reports. The research methodology employed includes exploratory, descriptive narrative, and bibliometric methods, based on a review of previously published research. We conducted a bibliometric analysis of 158 publications associated with Sustainable Development Goals and sustainability reports available in the Scopus database from 2017 to 2023 to quantitatively and qualitatively explore this research field. The study utilized the R-studio bibliometrics package.The results demonstrate that the integration of SDGs into Sustainability Reports is a crucial step for companies to measure, report, and improve their social, economic, and environmental impacts while contributing to the achievement of sustainable development goals. These findings imply the need for regulatory bodies to further enhance their role in strengthening the importance of companies in achieving SDGs.